L-arabinose alleviates constipation through gastrointestinal peptide，gut microbiota，and Phlpp2 of gastrointestinal rhythms in rats - Ting Gong; Linzheng Liao; Yong Tang; Weiwei Liu; Ling Yao; Zhen Wu; Jianmei Li; Fulai Bai; Qian Zhang; Liling Tang (Journal of Functional Foods)
Constipation is a common gastrointestinal disorder, and while L-arabinose has been shown to relieve it, the exact molecular mechanisms remain unclear. This study investigated the effects of L-arabinose in constipated rat at doses of 400, 600, and 800 mg/kg body weight (B.W.). The 800 mg/kg B.W. dose significantly improved overall physiological state, stool consistency, intestinal transit, and gastric emptying. It also improved gastric, liver, and kidney function, while modulating key gastrointestinal peptides, including motilin (MTL), substance P (SP), vasoactive intestinal peptide (VIP), acetylcholinesterase (AchE), endothelin-1 (ET-1), serotonin (5-HT), somatostatin (SS), gastrin (Gas), and nitric oxide (NO). In addition, the 800 mg/kg dose notably increased goblet cell numbers, mucus layer thickness, and beneficial gut microbes such as Ruminococcus flavefaciens and Muribaculum intestinale. It also upregulated the expression of Cd38, Phlpp2, Muc3, and Acat2, while downregulating Cd34, C1qa, and C1qc. These results indicate that L-arabinose not only alleviates constipation but also enhances immune function and regulates signaling pathways, restoring gastrointestinal peptides to near-normal levels.